PENGARUH PERCIEVED QUALITY, CORPORATE IMAGE, PERCEIVED VALUE YANG DI MEDIASI OLEH CUSTOMER SATISFACTION TERHADAP BRAND LOYALTY PADA PENGGUNA SMARTPHONE MEREK IPHONE (STUDI KASUS PADA GEN Z DI SURABAYA) - Azmil Chusnaini; Reizano Amri Rasyid; Candraningrat Candraningrat (Media Mahardhika, 2022)
The purpose of this paper is to examine the effect of perceived quality through mediating customer satisfaction in the context of brand loyalty to iPhone smartphone users among the Z millennial generation in Surabaya. The first model examines the impact of perceived quality on brand loyalty which is mediated by customer satisfaction; this second model investigates the impact of corporate image on brand loyalty mediated by customer satisfaction; and the final model examines the impact of perceived value on brand loyalty mediated by customer satisfaction. The methodology design of a three conceptual model approach was developed based on the existing literature. These models are validated through a quantitative approach, analyzed using regression analysis with SmartPLS. The sampling technique in this study used nonprobability sampling using a purposive sampling approach. This study is a development of previous studies that tested customer satisfaction variables as a mediator of brand loyalty. It is hoped that this research can contribute to literature by becoming additional research that studies the mediating effects of customer satisfaction on company image, perceived value, and perceived quality, as well as examining their relationship with brand loyalty in the context of Iphone brand smartphone products in the Z millennial generation in Surabaya.